2007
DOI: 10.3923/pjbs.2007.2595.2598
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Genetic Effects on Early Growth Traits in Moghani Sheep Breeds

Abstract: The effects of environmental factors on early growth traits (birth weight, weaning weight, body weight at 6 months of age and daily gain from birth to weaning and weaning to 6 months of age) using 10432 records in Moghani sheep breed were studied and Genetic and Environmental variance component were estimated using 8468 records of Jafarabad Animal Breeding Station from 1999 to 2004. Birth year on all traits and dam age had significant effect only for birth and weaning weight. Sex of lambs and birth type had no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…This may be due to the limited sample size population used in the present study. In agreement, the sex of the animal had no significant effect on the growth traits in other sheep breeds such as the Moghani breed [43]. Conversely, other studies have reported a significant effect of sex on growth traits [37,44].…”
Section: Discussionmentioning
confidence: 52%
“…This may be due to the limited sample size population used in the present study. In agreement, the sex of the animal had no significant effect on the growth traits in other sheep breeds such as the Moghani breed [43]. Conversely, other studies have reported a significant effect of sex on growth traits [37,44].…”
Section: Discussionmentioning
confidence: 52%